Une étude des tenants et aboutissants des articles 271 et 272 de la Loi sur la protection du consommateur - Dumais, Claude-René (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The new Consumer's Protection Act came wholly into force on April 30, 1981 under the title of Chapter P 41.1 of the Q.R.S., replacing and clarifying the former Consumer's Protection Act enacted in 1974 as Chapter 74. The new Act goes so far as to change some century-old rules of the Civil Code, including the law of proof, all in favour of a better deal for the consumer. In almost every case of abuse or violation of any section of the Act, the consumer must simply prove that the merchant violated one or more of its sections in order that penalties of sections 271 and 272 apply. The types of applicable penalties depend on the offence : Did the businessman simply overlook what the Act considers a mere formality ? Then the contract is voidable where a defence of lack of interest lies. Did the businessman contravene what the Act considers a fundamental right of the consumer? The consumer has a choice of remedies : — execution of the obligation by a third party ; — reduction of costs ; — annulment or resolution of the contract, the whole with a possible demand of damages, real and exemplary. The article explains the differences between form and substance as accepted by statute or case law, and the solutions applied. The correlation with other parts of the Civil Code, untouched by the Consumer Protection Act, is also studied, both in matters of proof, intent, and possible unjust enrichment of the consumer.